Effect Of Perception Of Usability And Perception Of Ease Of Use Of Digital Payment On The Performance Of Cashless Society Programs In The Management Of State Finances - Gede Sayang Adi Yadnya, I Dewa (Riviera Publishing, 2022)
This study aims to understand the effect of perceptions of usability and perceptions of ease of use of digital payment on the performance of the Cashless Society program in the financial management of the transaction state as a new 4.0 business behavior that is supported by Cashless Society 5.0. Until now, digital competencies, demographics, and infrastructure in Indonesia in implementing cashless economies are not optimal. This study uses a descriptive-qualitative approach with the literature study method. The purpose of the study to determine the development of the Cashless Society transaction behavior in the management of state financial results stated that Cashless and Cardless Transaction behaviors have been running, it is a business behavior that can provide economic added value and become an alternative solution to economic problems in Indonesia. Indonesia's readiness to be cashless society still requires support from various parties to megoptalize financial and digital literacy.